PENGARUH PEMBELAJARAN MENGGUNAKAN MEDIA GEOGEBRA TERHADAP KECEMASAN MATEMATIKA DAN MOTIVASI SISWA SD NEGERI 040461 BERASTAGI - Simamora, Indah; Br Sitepu, Feriti Nantasya (JURNAL CURERE, 2023)
Most students find mathematics difficult because of its abstract nature. Especially in areas of spatial shapes that cannot be completed manually. This can have an impact by increasing students' math anxiety and reducing student motivation. So media is needed that can visualize abstract problems in mathematics. Geogebra is a program that allows students to get intuitive feelings and imagine mathematical processes. The aim of this research is to see the effect of using Geogebra media on students' anxiety and motivation in learning mathematics at State Elementary School 040461. This research is a quasi-experiment. This research was carried out at SD Negeri 040461 Berastagi. The population of this research is all students at SD Negeri 040461 Berastagi for the 2022/2023 academic year. The research sample was carried out using a random sampling technique, namely drawing lots to get the experimental class and the control class. The sample used is class VA and VB students. The use of geogebra media is taught in the experimental class while the control class uses conventional methods. The mathematical material used is spatial figures. Data were collected using anxiety and motivation questionnaires as well as tests at the posttest. Descriptive and inferential statistical methods were used to analyze data using SPSS. Descriptive and inferential statistical methods were used to analyze data using SPSS. Descriptive statistics are used to see the average and standard deviation. Inferential analysis is used for Multivariate Covariance (MANCOVA). The results showed that there was a significant difference between anxiety and mathematics motivation, where the average score of the experimental group was greater than the control group. The use of geogebra learning can influence students  anxiety and motivation at SD Negeri 040461 in mathetics.